Balancing Benefits and Risks of Immortal Data: Participants' Views of Open Consent in the Personal Genome Project. Issue 1 (17th December 2015) - Zarate, Oscar A.; Brody, Julia Green; Brown, Phil; Ramirez‐Andreotta, Monica D.; Perovich, Laura; Matz, Jacob
Abstract: An individual's health, genetic, or environmental‐exposure data, placed in an online repository, creates a valuable shared resource that can accelerate biomedical research and even open opportunities for crowd‐sourcing discoveries by members of the public. But these data become "immortalized" in ways that may create lasting risk as well as benefit. Once shared on the Internet, the data are difficult or impossible to redact, and identities may be revealed by a process called data linkage, in which online data sets are matched to each other. Reidentification (re‐ID), the process of associating an individual's name with data that were considered deidentified, poses risks such as insurance or employment discrimination, social stigma, and breach of the promises often made in informed‐consent documents. At the same time, re‐ID poses risks to researchers and indeed to the future of science, should re‐ID end up undermining the trust and participation of potential research participants. The ethical challenges of online data sharing are heightened as so‐called big data becomes an increasingly important research tool and driver of new research structures. Big data is shifting research to include large numbers of researchers and institutions as well as large numbers of participants providing diverse types of data, so the participants' consent relationship is no longer with a person or even a research institution. In addition, consent is further transformed because big data analysis often begins with descriptive inquiry and generation of a hypothesis, and the research questions cannot be clearly defined at the outset and may be unforeseeable over the long term. In this article, we consider how expanded data sharing poses new challenges, illustrated by genomics and the transition to new models of consent. We draw on the experiences of participants in an open data platform—the Personal Genome Project—to allow study participants to contribute their voices to inform ethical consent practices and protocol reviews for big‐data research.